A ingestão de uma dose de suco de beterraba não reduz a pressão arterial mediada por uma sessão de exercício aeróbio em mulheres hipertensas após a menopausa: um estudo cruzado, aleatorizado, duplo-cego e placebo controlado - Ribeiro, Ana Luiza Amaral (2019)
Introduction: The climacteric consists of the woman transition from the reproductive to the non-reproductive phase, and this is due to the reduction of estrogen production by the ovaries, which consequently can generate a greater predisposition for the development of cardiovascular diseases, among them hypertension. The disease treatment is primarily medicated, but there are indications that certain specific foods, such as beet juice that is rich in nitrate (nitric oxide precursor), can bring benefits to this population, especially when associated with physical exercise. Objective: To verify if an acute intake of beetroot juice potentiates post-exercise hypotension (PEH) in hypertensive postmenopausal women. Methods: 13 hypertensive postmenopausal women (58.1±4.62 years and 27.4±4.25 kg/m² of BMI) were recruited to participate in three experimental sessions, taking three different beverages: beetroot juice (BJ), placebo – BJ nitrate-depleted (PLA), and orange flavored non-caloric drink (OFD). The participants performed a moderate aerobic exercise training on a treadmill, at 65-70% of heart rate reserve (HRR), for 40 minutes. The protocol started at 07h, after an overnight fast, when the first resting blood pressure (BP) was measured. The beverage was ingested at 07h30 and BP was monitored until the exercise training started, at 09h30. After the end of the exercise session, BP was measured every 15 minutes over a 90-minute period. Saliva samples were collected at rest, immediately before and after exercise, and 90 minutes after exercise for nitrite (NO2-) analysis. Results: There was an increase in salivary NO2- with BJ intake when compared to OFD and PLA. A slight increase in salivary NO2- was observed with PLA when compared to OFD (p <0.05), however, PLA was still lower when compared to BJ (p<0.001). There were no changes in salivary NO2- with the OFD. Systolic and diastolic BP decreased (p<0.001) on all post exercise time points after all interventions, with no difference between the three beverages. Conclusion: Acute BJ intake does not change PEH responses in hypertensive postmenopausal women, even with increased NO2-/NO bioavailability.